Depiction of identity disorientation and sexual barbarity: Analysing the racial degradation in Toni Morrison’s The Bluest Eye and Beloved - Tasnim, Sumaiya (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2020.